Biodistribution and Imaging of The 99mTc-Glutathione Radiopharmaceutical in White Rats Induced with Cancer - H. Wongso; N. Zainuddin; Iswahyudi Iswahyudi (Atom Indonesia, 2013)
99mTc-glutathione (99mTc-GSH) is a radiopharmaceuticalwhich is potentially used as a cancer diagnostic kit. As with other radiopharmaceuticals, before applied in humans, including in clinical trials, 99mTc-GSH needs to go through a series of preclinical trials in animal first. The preclinical trial which has been done in this study is the evaluation of the biological test on biodistribution and imaging of white rats (Rattus norvegicus) which had been induced with cancer. The aims of this research were to obtain data on biodistribution and to image the biodistribution of 99mTc-GSH at 1 hour, 3 hours, and 24 hours post-injection. Biodistribution resultsof 99mTc-GSHin the cancer at the timesof 1 hour, 3 hours, and 24 hours after injection were 0.66% ID/g, 0.95% ID/g, and 0.06% ID/g, respectively. This result shows that the highest accumulation of 99mTc-GSH in canceroccur at 3 hours post-injection. This value indicates that the optimal accumulation of the 99mTc-GSH occur in this time interval.In addition, the results of imaging test also show that the accumulation capacity of 99mTc-GSHin cancer is also highest at 3 hours post-injection.Received:16 January 2013; Revised:15 October 2013; Accepted: 16 October 2013